Validation of High-Performance Liquid Chromatography Method for Determination of Vitamin B1 in Powder Milk - Supriyono Supriyono; Mudhiah Fitrillah; Arie Pratama Putra (Jurnal Kimia Sains dan Aplikasi, 2020)
Vitamin B1 plays an important role in the co-enzymatic reactions for energy-rich compounds called ATP (Adenosine Tri Phosphate). Therefore, it should be added to various food products, for example, milk powder. One method that can be used to determine vitamin B1 is SNI number 3751: 2009, but the method is intended for wheat flour. If the method is to be used for the analysis from other samples, such as milk powder, optimization, and validation, are needed. This experiment was carried out using HPLC, C18 column, and UV detector with a wavelength of 254 nm. The mobile phase used is methanol: acetic acid: bi-distilled water = 32:1:67 (v/v/v), flow rate = 1 mL/minute, isocratic, and reverse phased technique. Method validation parameters include tests of system suitability, linearity, the limit of detection, the limit of quantitation, precision (repeatability), and accuracy. The results showed that the system suitability test was obtained relative standard deviations (% RSD) for retention time and peak area, tailing factor, resolution, separation factor was 0.297%, 1.476%, 1.113, 6.693, and 4.406 respectively. The validation test gets a correlation coefficient (R) of 0.9996, the limit of detection and limit of quantitation were 0.0122 mg/100 mL and 0.0244 mg/100 mL, respectively. The precision test obtained Horwitz's ratio of 0.27%. Accuracy test using CRM obtained % recovery of 93.79-97.77%. All these results meet the requirements of method validation, so it can be concluded that the method of SNI number 3751: 2009 is valid for the determination of vitamin B1 in milk powder and can be used for routine analysis procedure.